Analytic Filmmaking: A New Approach to Research and Publication in the Social Sciences. Issue 3 (September 2014) - Germano, Roy
<x content-type="archive" xml:space="preserve">Abstract</x> New digital video technologies are transforming how people everywhere document, publish, and consume information. As knowledge production becomes increasingly oriented towards digital/visual modes of expression, scholars will need new approaches for conducting and publishing research. The purpose of this article is to advance a systematic approach to scholarship called analytic filmmaking. I argue that when filming and editing are guided by rigorous social scientific standards, digital video can be a compelling medium for illustrating causal processes, communicating theory-driven explanations, and presenting new empirical findings. I furthermore argue that analytic films offer policymakers and the public an effective way to glean insights from and engage with scholarly research. Throughout the article I draw on examples from my work to demonstrate the principles of analytic filmmaking in practice and to point out how analytic films complement written scholarship.